Plant diversity induces shifts in the functional structure and diversity across trophic levels. Issue 2 (4th September 2017) - Ebeling, Anne; Rzanny, Michael; Lange, Markus; Eisenhauer, Nico; Hertzog, Lionel R.; Meyer, Sebastian T.; Weisser, Wolfgang W.
Abstract : Changes to primary producer diversity can cascade up to consumers and affect ecosystem processes. Although the effect of producer diversity on higher trophic groups have been studied, these studies often quantify taxonomy‐based measures of biodiversity, like species richness, which do not necessarily reflect the functioning of these communities. In this study, we assess how plant species richness affects the functional composition and diversity of higher trophic levels and discuss how this might affect ecosystem processes, such as herbivory, predation and decomposition. Based on six different consumer traits, we examined the functional composition of arthropod communities sampled in experimental plots that differed in plant species richness. The two components we focused on were functional variation in the consumer community structure (functional structure) and functional diversity, expressed as functional richness, evenness and divergence. We found a consistent positive effect of plant species richness on the functional richness of herbivores, carnivores, and omnivores, but not decomposers, and contrasting patterns for functional evenness and divergence. Increasing plant species richness shifted the omnivore community to more predatory and less mobile species, and the herbivore community to more specialized and smaller species. This was accompanied by a shift towards more species occurring in the vegetation than in the ground layer. Our study shows that plant species richness strongly affects the functional structure and diversity of aboveground arthropod communities. The observed shifts in body size (herbivores), specialization (herbivores), and feeding mode (omnivores) together with changes in the functional diversity may underlie previously observed increases in herbivory and predation in plant communities of higher diversity.